Analisis Pengaruh Kompetensi, Lingkungan Kerja, Kompensasi dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan PT Klinis Eka Surya Yogyakarta - Tyas Kingkin Budiyanti (FE Program Studi Manajemen, 2022)
This study aims to determine of effect of competence, work environment, compensation and work motivation on employee performance. This research taking location by the number of respondents as many 47 employees.This type of research is descriptive quantitative research and data analysis using SPSS version 21.0. The sampling technique used is the accidental sampling method with data testing techniques used in the study include validity and reliability tests. Multiple regression analysis, to test and prove the hypothesis. The results showed that competence (X1) affects the variable (Y) work performance with a coefficient value of 3,206 > 2,018, work environment (X2) 4,283 > 2,018, compensation (X3) 2,039 > 2,018 and work motivation (X4) of 5,981 > 2,018.